Contemporary Concepts of Digital Marketing Campaigns: Artificial Intelligence and Environmental Responsibility - Todorovic, Brankica (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
In the context of digital transformation, digital marketing campaigns are implemented as an integral part of digital business models. Within these models, companies adopt omnichannel management approaches that integrate digital and physical channels, providing customers with a seamless, consistent, and connected experience. This paper examines key performance indicators of digital marketing campaigns with diverse objectives, including environmental responsibility, the enhancement of environmental awareness, and other socially relevant issues, as well as the relationship between investment levels and target audiences. The analysis is conducted through a case study of campaigns implemented by Costa Coffee. In addition, the paper analyses key performance indicators and critical responses to a digital marketing campaign created with the support of artificial intelligence, using the example of Coca-Cola. The study applies a qualitative research methodology based on a descriptive-analytical approach and the analysis of secondary data sources. A case study method and comparative analysis are employed to examine the advantages, limitations, and potential risks associated with the use of artificial intelligence and environmentally oriented campaigns in comparison with other forms of digital marketing campaigns.